2022
DOI: 10.3389/falgy.2022.889879
|View full text |Cite
|
Sign up to set email alerts
|

Adult Food Protein-Induced Enterocolitis Syndrome

Abstract: Food protein-induced enterocolitis syndrome (FPIES) is a non-IgE, cell-mediated food allergy, commonly diagnosed in infants and young children. In recent years, new-onset adult FPIES has been recognized. The underlying pathogenic mechanism of FPIES has yet to be elucidated, thus disease-specific diagnostic biomarkers have yet to be determined and an oral food challenge (OFC) remains the gold-standard for the diagnosis. Pediatric patients with FPIES classically present with symptoms of delayed, repetitive vomit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Weltweit gibt es einige Fallsammlungen zu erwachsenen FPIES-Patienten, bei denen Meeresfrüchte, Fisch und Ei als Trigger berichtet werden [15,16]. Dass das auslösende Nahrungsmittel zu einem früheren Zeitpunkt im Leben vertragen wurde, ist bei FPIES nicht ungewöhnlich [4]. Die Behandlung besteht in der Einhaltung einer vollständigen Allergenkarenz.…”
Section: Phänotypenunclassified
See 1 more Smart Citation
“…Weltweit gibt es einige Fallsammlungen zu erwachsenen FPIES-Patienten, bei denen Meeresfrüchte, Fisch und Ei als Trigger berichtet werden [15,16]. Dass das auslösende Nahrungsmittel zu einem früheren Zeitpunkt im Leben vertragen wurde, ist bei FPIES nicht ungewöhnlich [4]. Die Behandlung besteht in der Einhaltung einer vollständigen Allergenkarenz.…”
Section: Phänotypenunclassified
“…Häufige Auslöser von IgE-vermittelten Nahrungsmittelallergien wie Erdnuss oder Schalenfrüchte sind bei FPIES eine Rarität. Bei Erwachsenen sind Fisch und Meeresfrüchte mit Abstand die häufigsten Allergene [4]. Ei, Weizen und Milch sind berichtete, aber seltenere Allergene, wobei die meisten Daten aus internationalen Fallserien stammen [15,16].…”
Section: Auslöserunclassified
“…However, new-onset adult FPIES has been reported. 18 Nowak-Wegrzyn et al reported the first estimated prevalence of adult FPIES in the USA which was 0.22%. 19 Furthermore, González-Delgado et al reported the clinical characteristics of adult patients with FPIES where abdominal pain was the most common manifestation followed by diarrhea.…”
Section: Epidemiologymentioning
confidence: 99%
“…52 Cetinkaya et al in their prospective study that included 185 infants with FPIAP, non-IgE-mediated multiple-food allergies, using cow's milk formula before the symptoms emerged, concomitant IgE-related food allergy, and delay in timing of complementary feeding were reported as predictors for late tolerance development. 18…”
Section: Dovepressmentioning
confidence: 99%